Synthesis and Pesticidal Activities of 5-(2-Cyclopropylaminopyrimidin-4-yl)-4-(thiophenyl)thiazole Derivatives - Won-Sik Choi; Seok-Woo Nam; Il-Doo Kim; Seung-Han Kim; Kun-Ho Park; In-Kyung Bae; Eun-Sil Park; Hwang-Ju Jeon; Sung-Eun Lee (Journal of Chemistry)
Pesticidal activities of 4-[5-(2-cyclopropylaminopyrimidin-4-yl)-4-(4-chloro-2-fluoro-phenyl)thiazol-2-yl]-1-methylpiperidine, designated as Comp I, have been determined against a mosquito larva, Culex pipiens pallens, and a phytopathogenic fungus, Phytophthora capsici. Comp I was used as the leading compound in this study. The compounds were synthesized by reacting them with two functional groups, 3-thiophenyl and 2-thiophenyl groups, instead of 4-chloro-2-fluorophenyl group in Comp I. Other functional groups such as 2-aminothiazole, 2-(1-methylpiperazin-4-yl)thiazole, and 2-(piperazin-4-yl)thiazole were also introduced instead of 2-methylpiperidin-4-yl-thiazole of Comp I. Compounds designated as XIII-6~XV-7 were newly synthesized and their structures were confirmed by 1H- and 13C-NMR spectroscopy. Mosquito larvicidal activities of all the synthesized compounds against C. pipiens pallens were examined and Comp I among them showed the strongest larvicidal activity as 0.513 mM of LC50 value. The fungicidal activities of all the synthesized compounds against P. capsici were examined using the whole plant method. Among the XIII-6~XV-7 chemicals, 5-(2-cyclopropylaminopyrimidin-4-yl)-4-(thiophen-2-yl)thiazol-2-amine (VIII-6) showed the most potent antifungal activity in vivo. While the EC50 value of the commercial fungicide dimethomorph was 4.26 μM, EC50 of VIII-6 was 0.94 μM. Therefore, thiazole derivatives can be considered as viable candidates for the control of mosquito larvae and plant diseases.